Facile N≡N Bond Cleavage by Anionic Trimetallic Clusters V3−xTaxC4− (x=0–3): A DFT Study. Issue 3 (9th December 2021) - Wang, Ya‐Ya; Ding, Xun‐Lei; Gurti, Joseph Israel; Chen, Yan; Huang, Xue‐Qian; Li, Wei; Wang, Xin
Abstract: Activation of N2 on anionic trimetallic V3− x Ta x C4 − ( x= 0–3) clusters was theoretically studied employing density functional theory. For all studied clusters, initial adsorption of N2 (end‐on) on one of the metal atoms (denoted as Site 1) is transferred to an of end‐on: side‐on: side‐on coordination on three metal atoms, prior to N2 dissociation. The whole reaction is exothermic and has no global energy barriers, indicating that the dissociation of N2 is facile under mild conditions. The reaction process can be divided into two processes: N2 transfer (TRF) and N−N dissociation (DIS). For V‐series clusters, which has a V atom on Site 1, the rate‐determining step is DIS, while for Ta‐series clusters with a Ta on Site 1, TRF may be the rate‐determining step or has energy barriers similar to those of DIS. The overall energy barriers for heteronuclear V2 TaC4 − and VTa2 C4 − clusters are lower than those for homonuclear V3 C4 − and Ta3 C4 −, showing that the doping effect is beneficial for the activation and dissociation of N2 . In particular, V−Ta2 C4 − has low energy barriers in both TRF and DIS, and it has the highest N2 adsorption energy and a high reaction heat release. Therefore, a trimetallic heteronuclear V‐series cluster, V−Ta2 C4 −, is suggested to have high reactivity to N2 activation, and may serve as a prototype for designing related catalysts at a molecular level. Abstract : Activation of N2 is critical in nitrogen reduction reactions (NRR). The activation of N2 on trimetallic anionic clusters V3− x Ta x C4 − ( x= 0–3) was studied by density functional theory calculations. VTa2 C4 −, a heteronuclear cluster, can activate N2 through N2 transfer and N−N dissociation processes with low energy barriers.